2019
DOI: 10.1111/jep.13263
|View full text |Cite
|
Sign up to set email alerts
|

Using a structured, patient‐centred, educational exchange to facilitate a shared conversation about stroke prevention medications

Abstract: Objective The aim of this study was to investigate the feasibility of a structured patient‐centred educational exchange to facilitate a shared conversation about stroke prevention medications. Methods Participants (18 years or older) with a principal diagnosis of stroke or transient ischaemic attack were purposively sampled from the stroke unit of a 780‐bed teaching hospital in Australia and consented to participate in the study. A patient‐centred educational exchange was conducted face to face at the bedside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Feedback during the intervention phase related to either creating collaborative partnerships or utilizing feedback to refine the next iteration of the strategy. The final four studies actioned feedback only during the intervention phase (Ayton et al, 2017; Coombes et al, 2020; Girgis et al, 2017; Issac et al, 2018), utilizing an existing documented tool or health clinician developed program as the PCC strategy. Three of these studies (Coombes et al, 2020; Girgis et al, 2017; Issac et al, 2018) collected feedback for the direct purpose of cycling that information back into the PCC strategy itself to further individualize care, while Ayton et al (2017) expanded patient reported outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feedback during the intervention phase related to either creating collaborative partnerships or utilizing feedback to refine the next iteration of the strategy. The final four studies actioned feedback only during the intervention phase (Ayton et al, 2017; Coombes et al, 2020; Girgis et al, 2017; Issac et al, 2018), utilizing an existing documented tool or health clinician developed program as the PCC strategy. Three of these studies (Coombes et al, 2020; Girgis et al, 2017; Issac et al, 2018) collected feedback for the direct purpose of cycling that information back into the PCC strategy itself to further individualize care, while Ayton et al (2017) expanded patient reported outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…The vignettes provided a basis for collaborative clinician/patient workshops where potential organizational and educational strategies were generated to address local health literacy needs (Jessup et al, 2018). From a patient education perspective, Coombes et al (2020) trialed a patient-centered educational exchange (PC 3 EE) program, where patient feedback to questionnaires focused the education delivered by staff to the personalized needs of the patient following a stroke or transient ischemic attack.…”
Section: Resultsmentioning
confidence: 99%
“…Despite Ticaa’dom’s high one-on-one provider–client time, it was not more effective than the standard of care [ 37 ]. Telemedicine Guided Education [ 62 ], StrokeCoach [ 63 ], CEOPS [ 64 ] and a Structured Patient-Centered Educational Exchange [ 65 ] are all examples of ongoing research that utilize telephone follow-ups, which will potentially offer further insight into the efficacy of lower resource-intensive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] The edition concludes with a number of papers proposing innovative methods for implementing and evaluating the impact of PCC and SDM. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Again, the core concepts of PCC and SDM are explored across a very diverse set of contexts. It would of course be misleading to present this edition as the "conclusion" of the debate commenced in our previous thematic issue on this subject.…”
mentioning
confidence: 99%
“…The edition concludes with a number of papers proposing innovative methods for implementing and evaluating the impact of PCC and SDM . Again, the core concepts of PCC and SDM are explored across a very diverse set of contexts.…”
mentioning
confidence: 99%